The underclass - Auletta, Ken (Random House, 1982)
A first-hand account of America's new social dropouts--street criminals, hustlers, long-term welfare recipients and the homeless--and of what might be done to bring them into the mainstream"--Jacket subtitle. Includes material on the Manpower Demonstration Research Corporation.